Chromatographic analysis of ponatinib and its impurities: method development, validation, and identification of new degradation product - Wang, Jing; Zhu, Yonghong; Qin, Jisu; Wu, Wenyi; Huang, Rongrong; Cai, Liangliang (Frontiers in Chemistry, 2024)
Background: Ponatinib, a third-generation tyrosine kinase inhibitor, is employed in the management of adult chronic myeloid leukemia. Nevertheless, the presence of process impurities and degradation impurities linked to ponatinib may potentially influence its effectiveness and safety. Therefore, the objective of this research was to establish a robust liquid chromatography method and systematically validate it for the detection of substances related to ponatinib.The separation of ponatinib and its impurities was conducted using an Agilent 5HC-C18 chromatographic column (4.6 mm × 250 mm, 5 μm). The mobile phase A comprised a mixture of water and acetonitrile in a 9:1 ratio, with an aqueous solution of pH 2.4 containing 2 mM potassium dihydrogen phosphate and 0.4% triethylamine. Mobile phase B, consisting of acetonitrile, was eluted in a gradient fashion. The flow rate was set at 1.0 mL/min, detection wavelength at 250 nm, column temperature at 40 °C, and injection volume at 10 μL.The method demonstrated high specificity, sensitivity, solution stability, linearity, precision, accuracy, and robustness. Additionally, this research unveiled a novel compound, imp-B, generated via the oxidative degradation of ponatinib. The molecular structure of the newly discovered product was elucidated through the utilization of nuclear magnetic resonance (NMR) and high-resolution mass spectrometry (HRMS).In conclusion, the chromatographic method developed in this study has the potential to be utilized for the detection of ponatinib and its impurities, thereby offering significant insights for quality assessment in ponatinib research.